Implementation of Income Tax Policy on the Transfer of Ownership Rights to Land and/or Buildings in the Subsidized Housing Program in Bekasi Regency (Case Study of PT. Tata Bangun Sarana in 2020) - Marnani; Ahmed, Abdussalam Ali (Sinergi International Journal of Economics, 2023)
This study is motivated by the implementation of the Income Tax Policy on the transfer of ownership rights to Land and/or Buildings in the Subsidized housing Program. The government enforces a subsidized housing program with an income tax rate of only 1% and an exemption from value-added tax (VAT) of 0%. PT. Tata Bangun Sarana is one of the developers of subsidized housing in Bekasi Regency. The purpose of this study was to analyze the implementation carried out by PT. Tata Bangun Sarana on PP Number 34 of 2016 in the payment of the Income Tax Policy on the transfer of ownership rights to Land and/or Buildings as well as adjustment efforts due to the enactment of the regulation. This study uses two data sources, the results of interviews and documentation of PT. Tata Bangun Sarana which were analyzed using qualitative methods. PT. Tata Bangun Sarana has implemented PP No. 34 of 2016 during 2020. However, in June, July, and August, PT. Tata Bangun Sarana still imposed subsidized housing selling prices in accordance with PUPR Ministerial Decree No. 242/KPTS/M/2019 for the Bekasi regency area, which was Rp. 158,000,000 which should have used PUPR Ministerial Decree Number 535 of 2020, which was Rp. 168,000,000. PT. Tata Bangun Sarana is recommended to improve management in policy implementation to make it better, in the future to better anticipate interrelated regulations and policies so that there will be no tax underpayments in the future.